Efektivitas Pengelolaan Perpustakaan Keliling dalam Meningkatkan Minat Baca Masyarakat di Kantor Perpustakaan Arsip dan Dokumentasi Kota Padang - Meriana, Meriana; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
This article aims to describe how a mobile library management effectiveness in increasing public interest in KPAD; (2) Describe obstacles encountered in service in increasing public interest in KPAD bookmobile. The findings of the first study, the effectiveness of library management is a business that is achieved by a mobile library to achieve the goal, the goal of improving people's interest should also enhanced their knowledge towards the better. Second, faced in improving the public interest because of the lack of ministry officials visited the village library less because less satisfactory set time, society itself was less satisfying and less interest in reading inadequate facilities and infrastructure. Suggestions that should be done to optimize the effectiveness of library management in raising public interest is to improve the science community itself. One effort to do around the library as a means of informal education, source of knowledge and the dissemination of information is an appropriate means for the advancement of society. Keywords: management effectiveness; mobile library